Increasing the Production System Productivity Using Inertial Navigation - Bozek, Pavol; Nikitin, Yuri; Bezak, Pavol; Fedorko, Gabriel; Fabian, Michal (Manufacturing Technology Journal, 2015)
The paper addresses the integration of the inertial navigation unit implemented into the system of controlling the robot. It analyses dynamic properties of the sensors of the inertial unit, e.g. gyroscopes and accelerometers. The implementation of the original system of controlling the robot on the basis of autonomous navigation systems into the production system is a dominant part of the paper.
Keywords: production system; controlling; inertial navigation; robot